Comparative transcriptomics of a generalist aphid, Myzus persicae and a specialist aphid, Lipaphis erysimi reveals molecular signatures associated with diversity of their feeding behaviour and other attributes - Sharma, Manvi; Oraon, Praveen Kumar; Srivastava, Rakesh; Chongtham, Rubina; Goel, Shailendra; Agarwal, Manu; Jagannath, Arun (Frontiers in Plant Science, 2024)
Introduction Aphids are phloem sap-sucking insects and are a serious destructive pest of several crop plants. Aphids are categorized as “generalists” or “specialists” depending on their host range. Myzus persicae (Sulz.) is a generalist aphid with a broad host range while Lipaphis erysimi (Kalt.), a specialist aphid, has a narrow host range. Aphid infestation involves several sequential stages including host recognition and selection, overcoming primary plant defence barriers, feeding on phloem sap and detoxification of host defence responses. Information on the molecular basis of variations between generalist and specialist aphids with reference to the above processes is limited. Methods In the current study, we generated transcriptome data of M. persicae and L. erysimi from adult and nymph stages and analysed the differential expression of genes between adults of the generalist and specialist aphid and similarly, between nymphs of the two aphid species. We categorized these differentially expressed genes into nine different categories namely, chemosensation-related, plant cell wall degrading enzymes, detoxification-related, digestive enzymes, peptidases, carbohydrate-, lipid-, amino acid-metabolism and reproduction. We also identified putative effector molecules in both M. persicae and L. erysimi from the transcriptome data, Results and discussion Gene expression analysis identified 7688 and 8194 differentially expressed unigenes at adult and nymph stages, respectively of M. persicae and L. erysimi. M. persicae showed significantly higher levels of expression in a greater number of unigenes (5112 in adults and 5880 in nymphs) in contrast to the specialist, L. erysimi (2576 in adults and 2314 in nymphs) in both developmental stages. In addition, M. persicae displayed a greater number (350 in adults and 331 in nymphs) of upregulated unigenes involved in important processes such as host recognition, plant cell wall degradation, detoxification, digestion and metabolism, which correlate with its dynamic and polyphagous nature in contrast to the specialist (337 in adults and 251 in nymphs). We also observed a greater number of putative effectors in M. persicae (948 in adults and 283 in nymphs) than L. erysimi (797 in adults and 245 in nymphs). Based on our analysis, we conclude that the generalist aphid, M. persicae has a more diversified and stronger arsenal of genes that influence its polyphagous feeding behaviour and effective response to plant defence mechanisms against insect-herbivory. Our study provides a compendium of such candidate genes that would be most useful in studies on aphid biology, evolution and control.